CTNI-03. A PHASE I/IIA, OPEN-LABEL STUDY OF THE BRAIN-PENETRANT PARP1-SELECTIVE INHIBITOR AZD9574 AS MONOTHERAPY AND IN COMBINATION IN PATIENTS WITH ADVANCED SOLID MALIGNANCIES (CERTIS1). (14th November 2022) - Mueller, Nancy; Luen, Stephen; Stupp, Roger; Chalmers, Anthony; Huang, Baisong; Squatrito, Massimo; Davies, Barry; Hamerlik, Petra; Yap, Timothy
Abstract: BACKGROUND: Currently approved Poly ADP-Ribose Polymerase (PARP) inhibitors (PARPi) selectively inhibit and trap both PARP1 and PARP2 (PARP1/2) at sites of single strand (ss) deoxyribonucleic acid (DNA) (ssDNA) damage, preventing ssDNA repair and leading to replication-dependent DNA double strand breaks. Recent data suggest that only inhibition of PARP1 is required for anti-proliferative effects, while PARP2 functions in the survival of haematopoietic stem and progenitor cells. These observations suggest that the inhibition and trapping of PARP 2 is not needed for anti-cancer effects, and may be a major driver of haematological toxicity observed. AZD9574 is a novel brain-penetrant PARPi that potently and selectively inhibits and traps PARP1, with the goal of delivering efficacious, less toxic, and more combinable PARPi. Furthermore, owing to its central nervous system penetration capability, AZD9574 may provide a new treatment option for patients with CNS malignancies or patients with brain metastases characterized by homologous recombination deficiency (HRD). METHODS: This is a first-in-human modular study primarily designed to evaluate the safety and tolerability of AZD9574 as monotherapy and in combination with anti-cancer agents at increasing dose levels in patients with advanced solid malignancies, followed by expansion cohorts in specific indications. The study will also characterize the pharmacokinetics of AZD9574 and explore potential biological activity by assessing pharmacodynamic and exploratory biomarkers and anti-tumour activity. Module 1 will enrol patients with advanced breast, ovarian, pancreatic or prostate tumours harbouring homologous recombination deficiencies. Module 2 will enrol patients with isocitrate dehydrogenase (IDH)1/2 mutated glioma.